Striper Wars: An American Fish Story - Russell Dick (Island Press, 2005)
When populations of striped bass began plummeting in the early 1980s, author and fisherman Dick Russell was there to lead an Atlantic coast conservation campaign that resulted in one of the most remarkable wildlife comebacks in the history of fisheries. As any avid fisherman will tell you, the striped bass has long been a favorite at the American dinner table; in fact, we've been feasting on the fish from the time of the Pilgrims. By 1980 that feasting had turned to overfishing by commercial fishing interests. Striper Wars is Dick Russell's inspiring account of the people and events responsible for the successful preservation of one of America's favorite fish and of what has happened since.